Biodiversity Offset Policy: A Sustainable Conservation Opportunity - Rian Vebrianto; Alaniyah Syafarenr; Khairi; Suwondo; Yustina (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2018)
The ultimate goal of biodiversity offset is to avoid net loss and preferably net gain from species composition side, habitat structure, ecosystem function, community use, and cultural values related with biodiversity. The idea of biodiversity offset has created controversy for some conservation societies because there is concern that the use of this scheme may encourage governments to continue to allow projects that have a serious impact on biodiversity as long as the project offers compensation. This scheme could also allow the company to leave significant impacts on the project area as long as it holds conservation activities elsewhere. Therefore, the application of biodiversity offsets must strictly adhere to the mitigation hierarchy that places biodiversity offsets as the last resort after all possible efforts have been made to avoid and minimize the impact of the development project and restore biodiversity in the project area